Dunsoghly Castle Chapel, door jamb, arch and hood - O'Donovan, Danielle (My University, 2008)
Door jamb, arch and hood of the detatched castle chapel. Jamb and arch moulding from intrados comprise: hollow chamfer, right-angled rebate, quadrant. The hood, which is placed at some distance from the jamb, comprises from outside in: frontal fillet, hollow chamfer, right-angled rebate, hollow chamfer.
Door
Keywords: quadrant; Architecture, Gothic -- Ireland; Dublin (County); Tower houses; Gothic doorways; Late Medieval; moldings, hollow; roll moldings; hood moldings